Aplikasi Pupuk Mikro Boron dan Molibdenum pada Kualitas Buah Stroberi (Fragaria x ananassa Duch.) - Aditama, Ravi; Santosa, Edi; Kartika, Juang Gema; Nindita, Anggi; Rosyad, Astyani (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2025)
Indonesian strawberry quality is generally still low leading to high strawberry imports. Research aimed to evaluate the effect of Boron (B) and Molybdenum (Mo) applications on the production and quality of strawberries. The research was conducted at a farmer’s field in Rancabali-Bandung, Indonesia, from July to August 2024. Formulated foliar fertilizer containing 500 ppm B and 5 ppm Mo was applied with different concentrations (0%, 0.5%, 0.6%, 0.8%). It was applied at different fruit stages (5 and 12 days after anthesis). Data were evaluated for the number of fruits, fruit size and weight, and fruit quality. Results showed that application time at different fruit ages had no significant effect on all variables. Fertilizer concentration did not affect fruit production, but it affected fruit firmness, TTA, and TSS levels. The concentration of 0.8% resulted in the highest level of firmness, the lowest TAA level (0.32%), and the highest TSS (12.40 oBrix). Thus, the B and Mo applications enhanced some indicators of fruit quality in strawberries. It is important to evaluate the effect of B and Mo applications at the farmer’s level to enhance strawberry quality. Keywords: Acidity, Brix, foliar fertilizer, production, vitamin C